Ancestry dependent balancing selection of placental dysferlin at high-altitude - Gundling, William E.; Post, Sasha; Illsley, Nicholas P.; Echalar, Lourdes; Zamudio, Stacy; Wildman, Derek E. (Frontiers in Cell and Developmental Biology, 2023)
The placenta mediates fetal growth by regulating gas and nutrient exchange between the mother and the fetus. The cell type in the placenta where this nutrient exchange occurs is called the syncytiotrophoblast, which is the barrier between the placenta and maternal blood. Residence at high-altitude is strongly associated with reduced 3rd trimester fetal growth and increased rates of complications such as preeclampsia. We asked whether altitude and/or ancestry-related placental gene expression contributes to differential fetal growth under high-altitude conditions, as native populations have greater fetal growth than migrants to high-altitude. We have previously shown that methylation differences largely accounted for altitude-associated differences in placental gene expression that favor improved fetal growth among high-altitude natives (Gundling et al., 2018). We tested for differences in DNA methylation between Andean and European placental samples from Bolivia (La Paz (~3,600 m) and Santa Cruz, Bolivia (~400 m)). One group of genes showing significant altitude-related differences are those involved in cell fusion and membrane repair in the syncytiotrophoblast. Dysferlin (DYSF) shows greater expression levels in high- vs. low-altitude placentas, regardless of ancestry. DYSF has a single nucleotide variant (rs10166384;G/A) located at a methylation site that can potentially stimulate or repress DYSF expression. Following up with individual DNA genotyping in an expanded sample size, we observed three classes of DNA methylation that corresponded to individual genotypes of rs10166384 (A/A < A/G < G/G). We tested whether these genotypes are under Darwinian selection pressure by sequencing a ~2.5 kb fragment including the DYSF variants from 96 Bolivian samples and compared them to data from the 1000 genomes project. We found that balancing selection (Tajima’s D=2.37) was acting on this fragment among Andeans regardless of altitude, and in Europeans at high-altitude (Tajima's D=1.85). This supports that balancing selection acting on dysferlin is capable of altering DNA methylation patterns based on environmental exposure to high-altitude hypoxia. This finding is analogous to balancing selection seen frequency-dependent selection, implying both alleles are advantageous in different ways depending on environmental circumstances. Preservation of the adenine (A) and guanine (G) alleles may therefore aide both Andeans and Europeans in an altitude dependent fashion.